Modified laparoscopic simple prostatectomy combined with temporary internal iliac arteries clamping and urethrocystoanastomosis for large-volume benign prostatic hyperplasia: evaluation of efficacy and safety - S. N. Volkov; D. Yu. Pushkar; K. B. Kolontarev; V. S. Stepanchenko; V. I. Tereshchenko; A. R. Dzharimok; E. N. Andreeva; O. R. Grigoryan; A. E. Shevyakina; M. A. Daurov (Вестник урологии, 2023)
Introduction. Laparoscopic simple prostatectomy is the method of choice for surgical treatment of large-volume benign prostatic hyperplasia (BPH). However, the existing limitations of standard approaches are the reason for the development of new modifications.Objective. To evaluate the efficacy and safety of a modified laparoscopic simple prostatectomy (LSP), supplemented by temporary internal iliac arteries (IIA) clamping and vesicourethral anastomosis (VUA).Materials & methods. This multicenter open study included 195 patients (mean age 68.1 ± 6.4 years) who underwent LSP combined with temporary IIA clamping and VUA. The primary efficacy criterias during one follow-up year were the severity of urinary symptoms (IPSS), quality of life, maximum flow rate and post-void residual volume. All complications that developed during the 12-month postoperative follow-up period were registered. Statistical calculations were performed using IBM SPSS 23.2 software.Results. The average surgery time was 91.5 ± 23.2 minutes. Complications of Clavien-Dindo I, II, III grades were noted in 1.0%, 1.0% and 3.6% of patients, respectively; no complications of group IV developed. The mean bed-days were 5.2 ± 1.5 days, the decrease in hemoglobin was 0.6 ± 1.1 g/dL. No patient needed to use an irrigation system. Based on the results of 12 months postoperative follow-up, positive dynamics was established for average IPSS score (p = 0.003), QoL (p = 0.035), maximum urine flow rate (p = 0.012), residual urine volume (p = 0.004). The maximum urine flow rate one year after surgery reached 24.6 ± 2.8 ml/s, the post-void residual urine volume was 15.1 ± 11.9 ml, the average IPSS score was 9.1 ± 1.5, and the QoL score – 1.0 ± 0.7. During the 12-month follow-up period, a low amount of long-term complications was noted in 4 (2.1%) cases: 3 (1.6%) patients had stress urinary incontinence, 1 (0.5%) patient had bladder neck contracture.Conclusion. Modified LSP combined with temporary IIA clamping and VUA is associated with favorable efficacy and safety profile of the intervention in patients with large-volume BPH.